Differences in Hospital Accreditation Assessment Across National Tuberculosis Programs: A Narrative Review - Safar M, Awal; Oktamianti, Puput (LPPM Universitas Respati Indonesia, 2024)
AbstractBackground: Hospital accreditation provides guidelines for implementing national program standards related to the reduction of tuberculosis morbidity. However, each accreditation body has a different interpretation of the established standards, resulting in variations in the assessment elements across these bodies.Objective: This research aims to identify differences in hospital accreditation institutions in assessing tuberculosis control programs, facilities and infrastructure provision, and services in the effort to control tuberculosis risk factors according to regulations.Method: The method used in this research is a narrative review method.Results: This study found that clear differences in approaches are evident among various accreditation institutions in evaluating factors related to improving tuberculosis services.Conclusion: Accreditation institutions differ in assessing the improvement of TB services. Their focus includes facilities, clinical practices, drug procurement, MDR-TB services, and case recording. There is variation in assessment from compliance with standards to field practice implementation. Evaluation methods also vary such as observation, document examination, and interviews. A holistic approach is important for assessing the quality of TB services at hospitals by considering various aspects.Keywords: Accreditation , Hospitals , Tuberculosis @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;@font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-536859905 -1073732485 9 0 511 0;p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US;p mso-style-priority:99; mso-style-link:"Normal \(Web\) Char"; mso-margin-top-alt:auto; margin-right:0cm; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US;span.NormalWebChar mso-style-name:"Normal \(Web\) Char"; mso-style-priority:99; mso-style-unhide:no; mso-style-locked:yes; mso-style-parent:""; mso-style-link:"Normal \(Web\)"; font-family:"Times New Roman",serif; mso-ascii-font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-hansi-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-font-kerning:0pt; mso-ligatures:none; mso-ansi-language:EN-US;.MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Aptos; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Aptos; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Aptos; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;.MsoPapDefault mso-style-type:export-only; margin-bottom:8.0pt; line-height:115%;div.WordSection1 page:WordSection1;